Blending Through-Space and Through-Bond π-π-Coupling in [2,2']-Paracyclophane-oligophenylenevinylene Molecular Wires - Wielopolski, Mateusz; Molina-Ontoria, Agustin; Schubert, Christina; Margraf, Johannes; Krokos, Evangelos; Kirschner, Johannes; Gouloumis, Andreas; Clark, Timothy; Guldi, Dirk Michael; Martin, Nazario (Journal of the American Chemical Society, 2013)
A series of ZnP-pCp-oPPV-C60 conjugates covalently connected through [2,2′]-paracyclophane-oligophenylenevinylene (pCp-oPPV) bridges containing one, two, and three [2,2′]-paracyclophanes (pCps) has been prepared in multistep synthetic procedures involving Horner–Wadsworth–Emmons olefination reactions and/or Heck type Pd-catalyzed reactions. Molecular modeling suggests that charge transfer is effectively mediated by the pCp-oPPVs through a predominant hole-transfer mechanism. Photophysical investigation supports molecular modeling and reveals two major trends. On one hand, C60 excitation of 1, 2, and 3 leads exclusively to charge transfer between pCp and C60 to afford a ZnP-(pCp-oPPV)•+-C60•– radical ion pair state without giving rise to a subsequent charge shift to yield the ZnP•+-pCp-oPPV-C60•– radical ion pair state. On the other hand, ZnP excitation of 1, 2, and 3 results in a rather slow charge transfer between ZnP and C60, after which the ZnP•+-pCp-oPPV-C60•– radical ion pair state evolves. In temperature-dependent ZnP fluorescence experiments, which were performed in the temperature range from 273 to 338 K, two domains are discernible: low and high temperature behaviors. In the low temperature range (i.e., below 30 °C) the rate constants do not change, suggesting that a superexchange mechanism is the modus operandi. In the high temperature range (i.e., >30 °C) the rate constants increase. Moreover, we find rather strong distance dependence for 1 and 2 and weak distance dependence for 2 and 3. A damping factor of 0.145 Å–1 is derived for the former pair and 0.012 Å–1 for the latter.
EAM Import::2019-03-13

Dendronized fullerene-porphyrin conjugates in ortho, meta, and para positions: A charge-transfer assay - Krokos, Evangelos; Schubert, Christina; Spaenig, Fabian; Ruppert, Michaela; Hirsch, Andreas; Guldi, Dirk Michael (Chemistry-An Asian Journal, 2012)
The physicochemical characterization, that is, ground and excited state, of a new series of dendronized porphyrin/fullerene electron donor-acceptor conjugates in nonaqueous and aqueous environments is reported. In contrast to previous work, we detail the charge-separation and charge-recombination dynamics in zinc and copper metalloporphyrins as a function of first- and second-generation dendrons as well as a function of ortho, meta, and para substitution. Both have an appreciable impact on the microenvironments of the redox-active constituents, namely the porphyrins and the fullerenes. As a matter of fact, the resulting charge-transfer dynamics were considerably impacted by the interplay between the associated forces that reach from dendron-induced shielding to dipole-charge interactions. Copyright © 2012 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.

Electron transfer through rigid organic molecular wires enhanced by electronic and electron–vibration coupling - Sukegawa, Junpei; Schubert, Christina; Zhu, Xiaozhang; Tsuji, Hayato; Guldi, Dirk Michael; Nakamura, Eiichi (Nature Chemistry, 2014)
Electron transfer (ET) is a fundamental process in a wide range of biological systems, photovoltaics and molecular electronics. Therefore to understand the relationship between molecular structure and ET properties is of prime importance. For this purpose, photoinduced ET has been studied extensively using donor–bridge–acceptor molecules, in which π-conjugated molecular wires are employed as bridges. Here, we demonstrate that carbon-bridged oligo-p-phenylenevinylene (COPV), which is both rigid and flat, shows an 840-fold increase in the ET rate compared with the equivalent flexible molecular bridges. A 120-fold rate enhancement is explained in terms of enhanced electronic coupling between the electron donor and the electron acceptor because of effective conjugation through the COPVs. The remainder of the rate enhancement is explained by inelastic electron tunnelling through COPV caused by electron–vibration coupling, unprecedented for organic molecular wires in solution at room temperature. This type of nonlinear effect demonstrates the versatility and potential practical utility of COPVs in molecular device applications.

Fullerene Van der Waals Oligomers as Electron Traps - Shubina, Tatyana; Sharapa, Dmitry; Schubert, Christina; Zahn, Dirk; Halik, Marcus; Keller, Paul A.; Pyne, Stephen G.; Jennepalli, Sreenu; Guldi, Dirk Michael; Clark, Timothy (Journal of the American Chemical Society, 2014)
Density functional theory calculations indicate that van der Waals fullerene dimers and larger oligomers can form interstitial electron traps in which the electrons are even more strongly bound than in isolated fullerene radical anions. The fullerenes behave like "super atoms", and the interstitial electron traps represent one-electron intermolecular σ-bonds. Spectroelectrochemical measurements on a bis-fullerene-substituted peptide provide experimental support. The proposed deep electron traps are relevant for all organic electronics applications in which non-covalently linked fullerenes in van der Waals contact with one another serve as n-type semiconductors.

Gating charge recombination rates through dynamic bridges in tetrathiafulvalene-fullerene architectures - Castellanos, Sonia; Vieira, Andre A.; Illescas, Beatriz M.; Sacchetti, Valentina; Schubert, Christina; Moreno, Javier; Guldi, Dirk Michael; Hecht, Stefan; Martin, Nazario (Angewandte Chemie International Edition, 2013)
An open and shut case: The competition between charge separation and recombination in artificial photosynthetic systems can be controlled by using photochromic dynamic bridge. The photoinduced opening and closing of the bridge mediates the electronic coupling between donor (D) and acceptor (A). Copyright © 2013 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.

Intramolecular versus intermolecular electronic interactions between [5,6]-open and [6,6]-closed C60 adducts with exTTF - Takano, Yuta; Schubert, Christina; Mizorogi, Naomi; Feng, Lai; Iwano, Azusa; Katayama, Mikimasa; Angeles Herranz, M.; Guldi, Dirk Michael; Martin, Nazario; Nagase, Shigeru; Akasaka, Takeshi (Chemical Science, 2013)
Intramolecular and intermolecular electronic interactions are important concepts for fabricating fullerene-based nanostructures such as bulk heterojunction (BHJ) solar cells and supramolecular assemblies. To ascertain differences of the molecular interactions depending on the electronic characteristics of the fullerene adducts, we have synthesized and investigated the [5,6]-open and [6,6]-closed adducts of C, which are covalently linked to π-extended tetrathiafulvalene (exTTF) by a flexible σ-bond chain. The two adducts were synthesized by means of cycloaddition reactions and were characterized using spectroscopic methods such as MALDI-TOF mass spectrometry and NMR spectroscopy. Electronic properties of the [5,6]-open and [6,6]-closed adducts were investigated in the ground and excited states using steady-state absorption spectroscopy, cyclic and differential pulse voltammetry (CV and DPV), fluorescence spectroscopy, and femtosecond time-resolved absorption spectroscopy. DFT calculations of the two adducts predict that the flexible bridge between C and exTTF enables a closer proximity than the interlayer distance of graphite (3.35 Å), which dictates considerable π-π interactions. In comparing the [5,6]- and [6,6]-adducts, it is noteworthy to mention that the [6,6]-adduct revealed longer lifetimes of the photochemically formed radical ion pair states than that of the [5,6]-adduct, which is in contrast to results of recent investigations related to the photodynamics of [5,6]- and [6,6]-adducts of C. Titration experiments using references, namely [5,6]- and [6,6]-PCBM, inferred that the [6,6]-adduct gives rise to stronger electronic interactions with exTTF than the [5,6]-adduct. Comprehensive understanding of the different molecular properties, which the [5,6]- and [6,6]-adducts exhibit, provides valuable information regarding the morphology and/or the electronic properties of C-based nanocomposites, such as C-based BHJ solar cells or supramolecular assemblies. © 2013 The Royal Society of Chemistry.

Molecular wires - impact of π-conjugation and implementation of molecular bottlenecks - Schubert, Christina; Margraf, Johannes; Clark, Timothy; Guldi, Dirk Michael (Chemical Society Reviews, 2015)
In this review we highlight recent progress in the field of photochemically and thermally induced electron transport through molecular bridges as integrative parts of electron donor-bridge-acceptor conjugates. The major emphasis is hereby on the design and the modular composition of the bridges. To this end, we will demonstrate that control over attenuation factors and reorganization energies, on one hand, as well as electronic and electron-vibration couplings, on the other hand, enables tuning electron transport over distances as short as 3.5 Å and as large as 50 Å by up to nine orders of magnitude. In terms of electron transport, the maximum extreme is given by carbon-bridged oligo-p-phenylenevinylenes of different lengths, while a zinc tetraphenylporphyrin free base tetraphenylporphyrin dyad constitutes the minimum extreme.
EAM Import::2019-03-12

Mono- and bis(pyrrolo)tetrathiafulvalene derivatives tethered to C 60: Synthesis, photophysical studies, and self-assembled monolayers - Solano, Marta Vico; Della Pia, Eduardo Antonio; Jevric, Martyn; Schubert, Christina; Wang, Xintai; Van Der Pol, Cornelia; Kadziola, Anders; Norgaard, Kasper; Guldi, Dirk Michael; Nielsen, Mogens Brondsted; Jeppesen, Jan O. (Chemistry - A European Journal, 2014)
A series of mono- (MPTTF) and bis(pyrrolo)tetrathiafulvalene (BPTTF) derivatives tethered to one or two C60 moieties was synthesized and characterized. The synthetic strategy for these dumbbell-shaped compounds was based on a 1,3-dipolar cycloaddition reaction between aldehyde-functionalized MPTTF/BPTTF derivatives, two different tailor-made amino acids, and C 60. Electronic communication between the MPTTF/BPTTF units and the C60 moieties was studied by a variety of techniques including cyclic voltammetry and absorption spectroscopy. These solution-based studies indicated no observable electronic communication between the MPTTF/BPTTF units and the C60 moieties. In addition, femtosecond and nanosecond transient absorption spectroscopy revealed, rather surprisingly, that no charge transfer from the MPTTF/BPTTF units to the C60 moieties takes place on excitation of the fullerene moiety. Finally, it was shown that the MPTTF-C 60 and C60-BPTTF-C60 dyad and triad molecules formed self-assembled monolayers on a Au(111) surface by anchoring to C 60. © 2014 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.
CRIS-Team Scopus Importer:2023-03-07
Keywords: cycloaddition; donor-acceptor systems; fullerenes; monolayers; tetrathiafulvalenes

Noncovalent functionalization of thiopyridyl porphyrins with ruthenium phthalocyanines - Lourenco, Leandro M. O.; Hausmann, Anita; Schubert, Christina; Neves, Maria G. P. M. S.; Cavaleiro, Jose A. S.; Torres, Tomas; Guldi, Dirk Michael; Tome, Joao P. C. (ChemPlusChem, 2015)
Preconditions for the design of efficient organic solar-light-converting systems are strong absorptions across the visible region, the capacity to funnel excited state energy by intermolecular energy transfer, and alternative association processes in the photoinduced electron transfer. In this context, thiopyridyl porphyrins (PorSPy) and ruthenium phthalocyanines (RuPcs) proved to be versatile building blocks for the construction of novel supramolecular Por-Pc hybrid systems (PorSPy-RuPc) by axial coordination at ruthenium. The thiopyridyl groups placed at the bay region of the porphyrins coordinate the RuPc dye. A notable redistribution of the electron density in the new heterochromophore structures evidences the electron-donating/-accepting communication between the two dyes in the supramolecular hybrids. These structural hybrids were investigated physicochemically by means of their ground and excited state reactivities. Photophysical investigation by time-resolved transient absorption, mainly fluorescence and femtosecond spectroscopy, evidenced efficient intermolecular energy transfer from the photoexcited central porphyrin to the peripheral phthalocyanines in the supramolecular multichromophore ensembles. The findings may give impetus for the design of interesting materials for solar-light-converting systems.
CRIS-Team Scopus Importer:2023-03-07
Keywords: donor-acceptor systems; phthalocyanines; porphyrins; ruthenium; supramolecular chemistry

Phase-Preserving 2R-Regeneration of an 80-Gb/s RZ-DQPSK, Signal by Using a Nonlinear Amplifying Loop Mirror - Cvecek, Kristian; Sponsel, Klaus; Stephan, Christian; Ludwig, R.; Schubert, Christina; Onishchukov, Georgy; Schmauß, Bernhard; Leuchs, Gerd (ECOC September, 2007)
The performance of a nonlinear amplifying loop mirror as a 2R regenerator for an 80-Gb/s RZ-DQPSK has been investigated. A significant eye-opening improvement and a negative power penalty of 2.6 dB have been obtained.
UnivIS-Import:2017-12-18:Pub.2007.tech.IE.LEH.phasep

Precise control of intramolecular charge-transport: The interplay of distance and conformational effects - Schubert, Christina; Wielopolski, Mateusz; Mewes, Lars-Hendrik; De Miguel Rojas, Gustavo; Van Der Pol, Cornelia; Moss, Kathryn C.; Bryce, Martin; Moser, Jacques E.; Guldi, Dirk Michael; Clark, Timothy (Chemistry - A European Journal, 2013)
A new series of donor-bridge-acceptor (D-B-A) compounds consisting of π-conjugated oligofluorene (oFL) bridges between a ferrocene (Fc) electron-donor and a fullerene (C) electron-acceptor have been synthesized. In addition to varying the length of the bridge (i.e., mono- and bi-fluorene derivatives), four different ways of linking ferrocene to the bridge have been examined. The Fc moiety is linked to oFL: 1) directly without any spacer, 2) by an ethynyl linkage, 3) by a vinylene linkage, and 4) by a p-phenylene unit. The electronic interactions between the electroactive species have been characterized by cyclic voltammetry, absorption, fluorescence, and transient absorption spectroscopy in combination with quantum chemical calculations. The calculations reveal exceptionally close energy-matching between the Fc and the oFL units, which results in strong electronic-coupling. Hence, intramolecular charge-transfer may easily occur upon exciting either the oFLs or Fcs. Photoexcitation of Fc-oFL-C conjugates results in transient radical-ion-pair states. The mode of linkage of the Fc and FL bridge has a profound effect on the photophysical properties. Whereas intramolecular charge-separation is found to occur rather independently of the distance, the linker between Fc and oFL acts (at least in oFL) as a bottleneck and significantly impacts the intramolecular charge-separation rates, resulting in beta values between β 0.08 and 0.19 Å. In contrast, charge recombination depends strongly on the electron-donor-acceptor distance, but not at all on the linker. A value of β (0.35±0.01 Å) was found for all the systems studied. Oligofluorenes prove, therefore, to be excellent bridges for probing how small structural variations affect charge transport in D-B-A systems. Finely tuned transfer: Chemical modification of the oligo-fluorene linkers between Fc and C units enables fine-tuning of photoinduced charge-transfer processes in new donor-bridge-acceptor conjugates (see illustration). Copyright © 2013 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.

Probing charge transfer in benzodifuran-C60 dumbbell-type electron donor-acceptor conjugates: Ground- and excited-state assays - Li, Hui; Schubert, Christina; Dral, Pavlo; Costa, Ruben Dario; La Rosa, Andrea; Thüring, Jürg; Liu, Shi-Xia; Yi, Chenyi; Filippone, Salvatore; Martín, Nazario; Decurtins, Silvio; Clark, Timothy; et al. (ChemPhysChem, 2013)
Rigid electron donor-acceptor conjugates (1-3) that combine π-extended benzodifurans as electron donors and C molecules as electron acceptors with different linkers have been synthesized and investigated with respect to intramolecular charge-transfer events. Electrochemistry, fluorescence, and transient absorption measurements revealed tunable and structure-dependent charge-transfer processes in the ground and excited states. Our experimental findings are underpinned by density-functional theory calculations. Dumbbell arrays: A benzodifuran (BDF) donor is for the first time fused to two C molecules by different linkers to form triads 1-3 (see figure). Their redox behavior, absorption, fluorescence emission, and photoinduced intramolecular charge-transfer events have been investigated experimentally and theoretically. The lifetime of the resulting charge-separated state varies distinctly with the polarity of the solvents and the distance between the BDF and C units. © 2013 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.

Rates and energetics of intramolecular electron transfer processes in conjugated metallofullerenes - Schubert, Christina; Rudolf, Marc; Guldi, Dirk Michael; Takano, Yuta; Mizorogi, Naomi; Angeles Herranz, M.; Martin, Nazario; Nagase, Shigeru; Akasaka, Takeshi (Philosophical Transactions of the Royal Society A-Mathematical Physical and Engineering Sciences, 2013)
In this paper, we report on the design, redox potentials, excited state energies and radical ion pair state energies in electron donor-acceptor conjugates comprising the electron-donating π-extended tetrathiafulvalene and several electron-accepting fullerenes. To this end, we contrast an empty fullerene, that is, C, with two endohedral metallofullerenes, that is, open-shell La@C and closed-shell La@C, in terms of charge separation and charge recombination dynamics. © 2013 The Author(s) Published by the Royal Society. All rights reserved.

Tuning the reorganization energy of electron transfer in supramolecular ensembles - metalloporphyrin, oligophenylenevinylenes, and fullerene - and the impact on electron transfer kinetics - Stangel, Christina; Schubert, Christina; Kuhri, Susanne; Rotas, Georgios; Margraf, Johannes; Regulska, Elzbieta; Clark, Timothy; Torres, Tomas; Tagmatarchis, Nikos; Coutsolelos, Athanassios G.; Guldi, Dirk Michael (Nanoscale, 2015)
Oligo(p-phenylenevinylene) (oPPV) wires of various lengths featuring pyridyls at one terminal and C-60 moieties at the other, have been used as molecular building blocks in combination with porphyrins to construct a novel class of electron donor-acceptor architectures. These architectures, which are based on non-covalent, directional interactions between the zinc centers of the porphyrins and the pyridyls, have been characterized by nuclear magnetic resonance spectroscopy and mass spectrometry. Complementary physico-chemical assays focused on the interactions between electron donors and acceptors in the ground and excited states. No appreciable electron interactions were noted in the ground state, which was being probed by electrochemistry, absorption spectroscopy, etc.; the electron acceptors are sufficiently decoupled from the electron donors. In the excited state, a different picture evolved. In particular, steady-state and time-resolved fluorescence and transient absorption measurements revealed substantial electron donor-acceptor interactions. These led, upon photoexcitation of the porphyrins, to tunable intramolecular electron-transfer processes, that is, the oxidation of porphyrin and the reduction of C-60. In this regard, the largest impact stems from a rather strong distance dependence of the total reorganization energy in stark contrast to the distance independence seen for covalently linked conjugates.